Child-Protection Systems - Kata Zsófia Prém, Laura Kovács-Berényi; Jakab, Nóra; Benyusz , Márta (2025)
Social rights constitute one of the most debated areas of human rights law and are regulated differently across states. Nevertheless, they play a fundamental role in ensuring human dignity and meaningful participation in society. Modern human rights theory increasingly recognizes that civil and political rights cannot be separated from economic, social, and cultural rights, as the enjoyment of individual freedoms often depends on a minimum level of social security and social empowerment. Consequently, the state has a responsibility to establish legal and institutional frameworks that guarantee social protection, secure basic living conditions, and support vulnerable individuals and groups.The protection of children represents one of the most important dimensions of social rights. According to the United Nations Convention on the Rights of the Child (CRC), every child has the right to grow up in a family environment whenever possible. When children are temporarily or permanently deprived of parental care, or when remaining in their family is contrary to their best interests, states are obliged to provide special protection and appropriate alternative care. While parents bear the primary responsibility for a child’s upbringing and development, public authorities must intervene when a child’s rights, welfare, or safety are at risk.An integrated child protection system places the child at the centre of all policies and interventions. Such a system is based on the principles and rights enshrined in the CRC and requires effective cooperation among all relevant sectors, including social welfare, education, healthcare, justice, law enforcement, civil society, communities, and families. The purpose of this coordinated approach is to prevent abuse, neglect, exploitation, and violence against children while ensuring timely protection and support when such risks arise. International organizations and the European Union have emphasized the importance of strengthening integrated child protection systems through multidisciplinary cooperation, family support services, prevention measures, and child-friendly responses.The UN Guidelines for the Alternative Care of Children provide an important framework for ensuring the rights and well-being of children who cannot remain with their families. The guidelines are based on two fundamental principles: necessity and suitability. The necessity principle requires that all reasonable efforts be made to prevent family separation and that alternative care be used only when genuinely needed. The suitability principle requires that any alternative care arrangement be tailored to the individual needs, circumstances, and best interests of the child. This includes ensuring appropriate living conditions, access to education and healthcare, qualified caregivers, and regular reviews of placement decisions. Priority should generally be given to family- and community-based solutions, while residential care should be used only when it represents the most appropriate option for the child concerned.Against this theoretical and normative background, the present volume examines alternative care systems and child protection frameworks from a comparative Central European perspective. The chapters explore the legal foundations of children’s rights, the organisation and functioning of child protection systems, and the practical implementation of alternative care measures in different national contexts. Particular attention is paid to the challenges faced by vulnerable children, the application of the best interests principle, and the identification of good practices that promote children’s well-being and development. By combining legal analysis with comparative insights, the volume seeks to contribute to a deeper understanding of how states can effectively fulfil their obligations towards children deprived of parental care and strengthen integrated child protection systems.In conclusion, social rights and child protection are closely interconnected. The principles of human dignity, solidarity, and social justice require states to provide effective protection for vulnerable groups, particularly children. Integrated child protection systems and high-quality alternative care arrangements are therefore not only legal obligations under international law but also essential components of a humane and inclusive society that promotes the well-being and development of every child.